Radiographic outcomes of femur fractures following SIGN Fin nailing in low- and middle-income countries - Birner, Zachary H.; Hetzel, Scott J.; Wilson, Nathaniel M.; Whiting, Paul S. (OTA international : the open access journal of orthopaedic trauma, 2021)
To measure the effectiveness of the Surgical Implant Generation Network (SIGN) Fin nail for achieving satisfactory postoperative radiographic alignment following femoral shaft fractures. Femoral shaft fractures stabilized with the SIGN Fin nail were identified using the SIGN Online Surgical Database. A random number generator was used to identify 500 femur fractures fixed within 6 weeks of injury for which postoperative radiographs were available. Fractures were classified using OTA/AO and Winquist-Hansen classification systems. Deviation from anatomic alignment was measured on anterior-posterior and lateral radiographs using an on-screen protractor tool. Other clinical variables recorded in the SIGN Online Surgical Database were also analyzed. Simple logistic regression was used to assess for associations between subject and surgical characteristics and misalignment status. Intra- and inter-rater agreement was assessed with intraclass correlation coefficient (ICC). The overall rate of malalignment >5° was 9.4%. Factors associated with increased incidence of malalignment include older age, increased time to surgery, distal diaphyseal location, closed (vs open) reduction, degree of comminution, and fracture classification. Intra-rater ICC was 0.70 (0.52, 0.82) in the coronal plane and 0.55 (0.32, 0.72) in the sagittal plane. Inter-rater ICC was 0.37 (0.08, 0.60) and 0.32 (0.05, 0.54), respectively. The SIGN Fin nail is an effective implant for fixation of femoral shaft fractures in resource-limited regions, achieving rates of satisfactory postoperative alignment comparable to that of the standard SIGN nail as well as femoral shaft fractures treated in North American Trauma Centers. Further research is required to investigate rotational alignment and long-term clinical outcomes for the SIGN Fin nail. IV.